Multicenter Validation of Histopathologic Tumor Regression Grade After Neoadjuvant Chemotherapy in Muscle-invasive Bladder Carcinoma. (December 2019) - Voskuilen, Charlotte S.; Oo, Htoo Zarni; Genitsch, Vera; Smit, Laura A.; Vidal, Alvaro; Meneses, Manuel; Necchi, Andrea; Colecchia, Maurizio; Xylinas, Evanguelos; Fontugne, Jacqueline; Sibony, Mathilde; Rouprêt, Morgan; et al.
Abstract : Response classification after neoadjuvant chemotherapy in muscle-invasive bladder carcinoma is based on the TNM stage at radical cystectomy. We recently showed that histopathologic tumor regression grades (TRGs) add prognostic information to TNM. Our aim was to validate the prognostic significance of TRG in muscle-invasive bladder cancer in a multicenter setting. We enrolled 389 patients who underwent cisplatin-based chemotherapy before radical cystectomy in 8 centers between 2010 and 2016. Median follow-up was 2.2 years. TRG was determined in radical cystectomy specimens by local pathologists. Central pathology review was conducted in 20% of cases, which were randomly selected. The major response was defined as ⩽pT1N0. The remaining patients were grouped into partial responders (≥ypT2N0-3 and TRG 2) and nonresponders (≥ypT2N0-3 and TRG 3). TRG was successfully determined in all cases, and interobserver agreement in central pathology review was high (κ=0.83). After combining TRG and TNM, 47%, 15%, and 38% of patients were major, partial, and nonresponders, respectively. Combination of TRG and TNM showed significant prognostic discrimination of overall survival (major responder: reference; partial responder: hazard ratio 3.5 [95% confidence interval: 1.8-6.8]; nonresponder: hazard ratio 6.1 [95% confidence interval: 3.6-10.3]). This discrimination was superior compared with TNM staging alone, supported by 2 goodness-of-fit criteria ( P =0.041). TRG is a simple, reproducible histopathologic measurement of response to neoadjuvant chemotherapy in muscle-invasive bladder cancer. Integrating TRG with TNM staging resulted in significantly better prognostic stratification than TNM staging alone. Abstract : Supplemental Digital Content is available in the text.